Um olhar sobre o uso das TIC no ensino de Física - Rigo, Jader Rodrigo Vieira (2014)
This paper presents an analysis of the use of Information and Communication Technologies (ICT) in Physics classes whose main objective will be to check the contributions of these resources in the classroom. Participate in the research students of the 1st year of high school in the State School of Basic Education Cicero Barreto. The realization of this theoretical study will involve the rescue of some basic concepts related to ICT resources found in official documents the articles of the area in question, as well as provide and test a proposed teaching through an instructional sequence (SD) with the aid of called learning cycle: Cycle Kolb, as the final product. This SD is divided into learning activities about the concept of Conservation of Mechanical Energy using some ICT resources, such as video, conceptual map and virtual forum on a website, structured with the aid of the four stages of Kolb Cycle . We chose to use this learning cycle by believing in their own potential and problematical character (contextualized, interdisciplinary and reflexive), and enable interaction and dialogue between students. Your application will be through access to video and website, designed specifically for this study via the Internet in the computer room of the school mentioned forming a Virtual Learning Environment (VLE). The site was built with the aid of the tool Google Sites. In addition to access video, text and summaries aided drafting tool is available at: libreoffice Impress, will be used as material for analysis, two questionnaires. One applied prior to the development of SD and another after development thereof. In addition, observations will be performed at the time of their interaction with students. Want to check the contribution of ICT to the use of the Kolb cycle as the organizer of the proposed activities in the process of Teaching and Learning Theme: Conservation of Mechanical Energy.